Revitalizing Halal Supervision in North Sulawesi: Addressing Synergy and Resource Gaps for Consumer Protection - Tri Susanti (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This policy research examines fundamental problems in the implementation of Law Number 33 of 2014 concerning Halal Product Assurance (UU JPH) in North Sulawesi Province (Sulut), where halal product supervision fails to optimally protect Muslim consumers. The main issue lies in weak institutional synergy and suboptimal resource allocation within the JPH supervision system. Theoretically, this problem is supported by the Bottom-Up Policy Implementation Theory and Collaborative Governance Theory, which point to dysfunctional collaborative governance at the local level. The in-depth analysis identifies two main root causes: First, the failure of synergy manifested through unclear division of operational authority between the Halal Product Assurance Organizing Agency (BPJPH) and Regional Apparatus Organizations (OPD), as well as data fragmentation that hinders integrated supervision. Second, fiscal and human resource gaps characterized by minimal regional budget allocation for JPH and the limited number and competence of certified JPH Supervisors. These human resource limitations make post-certification supervision reactive and eliminate the deterrent effect of sanctions mandated by Government Regulation No. 42 of 2024. Based on the USG analysis, the weak commitment of managers and the unclear sanction mechanism are priorities. Therefore, policy recommendations focus on regulations for integrating national data systems as a solution for efficient governance and increasing human resource capacity through local partnerships. The ultimate goal is to establish a coordinated JPH supervision system in North Sulawesi, supported by adequate resources, and ensuring legal certainty for consumers.